PERANCANGAN SISTEM MONITORING DOKUMENTASI PROBLEM SOLVING DENGAN CODEIGNITER (STUDI KASUS : ITI RSUD BANYUMAS) - Amirul Mukminin; Rizal Rachman; Marjito Marjito (STMIK Mardira Indonesia, Bandung, 2020)
The driving force for the advancement of science today is a complete past record in which future generations also learn from the natural phenomena that exist and the events that are going on at the present time. Will come where the period of knowledge becomes the cornerstone of human life that masters it. Documentation is very important to be a pillar of evaluation and decision making by future generations. So the documentation application that makes documentation and trounbleshoting is made easier and if the senior has retired the junior will easily find the data that will be used to make decisions. Often various viruses threaten the safety of the Hospital Information System (SIMRS) server, if it is not well documented, the Information Technology Installation must do a re-investigation with the same virus. So with this problem, a Web-based Banyumas Hospital ITI Documentation system was created using Ubuntu Server with Codeigniter and Postgresql where Codeigniter and Postgresql frameworks will give birth to a combination of superior speed and capacity. Keywords: Information Monitoring System, Documentation, WebsiteDOI : http://doi.org/10.5281/zenodo.3929057